2017
DOI: 10.4049/jimmunol.1600868
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Triggers a Dual Signaling Axis To Selectively Suppress Activated Human T Lymphocyte Migration

Abstract: H2O2 is an early danger cue required for innate immune cell recruitment to wounds. To date, little is known about whether H2O2 is required for the migration of human adaptive immune cells to sites of inflammation. However, oxidative stress is known to impair T cell activity, induce actin stiffness, and inhibit cell polarization. In this study, we show that low oxidative concentrations of H2O2 also impede chemokinesis and chemotaxis of previously activated human T cells to CXCL11, but not CXCL10 or CXCL12. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Higher concentrations of H2O2 (>10μM) inhibit chemotaxis and cause an elevated calcium concentration throughout the cell. In agreement, previous studies have also found inhibition of chemotaxis in neutrophils and lymphocytes at levels of H2O2 above 10μM 39,40 . A probable cause of the inhibition of chemotaxis at higher H2O2 is loss of the differential intracellular calcium gradient necessary for cell guidance, as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Higher concentrations of H2O2 (>10μM) inhibit chemotaxis and cause an elevated calcium concentration throughout the cell. In agreement, previous studies have also found inhibition of chemotaxis in neutrophils and lymphocytes at levels of H2O2 above 10μM 39,40 . A probable cause of the inhibition of chemotaxis at higher H2O2 is loss of the differential intracellular calcium gradient necessary for cell guidance, as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These include: (i) downregulation of expression of the signal-transducing ζ-chain of the T cell receptor for antigen, resulting in the loss of responsiveness of TILs to tumor antigens [76]; (ii) attenuation of activation of the transcription factor, nuclear factor-kappaB (NFκB), resulting in impaired cytokine production by T cells [77]; and iii) oxidation of the actin-remodeling protein, cofilin, which is involved in T cell activation and migration [63,78]. In addition, H 2 O 2 has been reported to inhibit T cell chemotaxis initiated by the inflammatory chemokine, CXCL11, which is achieved via decreased expression of CXCR3 and failure of associated intracellular signaling mechanisms [79].…”
Section: Pro-oxidative Mechanismsmentioning
confidence: 99%
“…Superoxide anions (O • -) and hydrogen peroxide (H O) are the principal mitochondrial ROS (mitoROS) essential for CD4 + T cell redox signaling [15, 23, 32]. Due to its permeability, H 2 O 2 serves as a secondary messenger molecule [3235]. For instance, exposed thiol moieties (-SH) on proteins can be oxidized by H 2 O 2 , altering protein conformation to favor either increases or decreases in enzymatic activities [36, 37].…”
Section: Introductionmentioning
confidence: 99%